Preferency of soil macrofauna to crops residue at different light intensity - SUGIYARTO SUGIYARTO; MANAN EFENDI; EDWL MAHAJOENO; YOGI SUGITO; EKO HANDAYANTO; LILY AGUSTINA (Society for Indonesian Biodiversity, 2007)
Every species of soil macrofauna prefer specific food and environment to be establish in it's habitat. Their diversity depend on variation of food and environmental condition. The aim of this research was to study the effect of different crop residue and light intensity on population of several soil macrofauna specieses. Mycrocosmos experiment was arranged in split-plot design with two treatments factor, i.e.: (1) crop residue (albizia, papaya, elephant grass, maize, sweet potato and without crop residue input), and (2) light intensities (0, 5, 15 and 25) Watt/day. The soil macrofauna were earthworms, millipedes, scarabids larvae and cocroachs.Results of the study showed that: (1) crop residues apllication increased soil macrofauna population, especially maize residue ( by 113%, respectively, compare to control tretment), (2) on higher light intensity, population of earthworms, scarabids larvae and cocroach decreased, but population of millipedes increased, (3) the highest macrofauna population was on maize residue and 5 Watt/day light intensity treatment.Â© 2007 Jurusan Biologi FMIPA UNS SurakartaKey words: Soil macrofauna, preferency, crop residue, light intensity